15.3k views
4 votes
Help me pleaseeeeeee?

Help me pleaseeeeeee?-example-1

2 Answers

2 votes

Answer:

-7x+3y+3

Explanation:

(4-5+4)=3

(-2x-5x)=-7x

(-4y+7y)=3y

User Simon Fraser
by
4.8k points
3 votes

For this case we must simplify the following expression:


4-5-2x-4y + 4-5x + 7y

We must combine similar terms, taking into account that equal signs are added and the same sign is placed, while different signs are subtracted and the sign of the greater is placed:


4-5 + 4-2x-5x-4y + 7y =\\3-7x + 3y

Answer:


3-7x + 3y

User James Render
by
5.4k points